Complete mitochondrial genome of banana skipper Erionota torus Evans (Lepidoptera: Hesperiidae) and phylogenetic analysis. Issue 7 (3rd July 2021) - Liu, Li-Na; Zeng, Li; Guo, Zhi-Xiang; Yang, Bao-Ming; Yin, Ke-Suo; Wang, Chun-Mei; Zheng, Si-Jun
Abstract: Erionota torus (Evans, 1941) is a banana pest and is mainly distributed in Southeast Asia and the Pacific regions. The complete mitogenome of E. torus (GenBank accession number MW586888) is 15, 987 bp in size, including 13 protein-coding genes, 22 transfer RNAs, 2 ribosomal RNAs genes, and a noncoding A + T-rich region. The A + T-rich region is located between 12S rRNA and tRNA Met . The base composition of the whole E. torus mitogenome is 39.68% for A, 7.30% for G, 41.55% for T, and 11.47% for C, with a high AT content of 81.23%. The phylogeny analysis indicated that E. torus had a close relationship with Notocrypta curvifascia . The present data could contribute to the further detailed phylogeographic analysis and provide a comprehensive control strategy for this banana pest.